2010
DOI: 10.2138/am.2010.3035
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure behavior of 2M1 muscovite

Abstract: The crystal structure and pressure influence (between 0-6 GPa) on 2M 1 muscovite have been calculated by quantum-mechanical methods based on density functional theory (DFT) with optimized numerical LCAO basis sets and norm-conserving pseudopotentials. Tensions between 0.8 and 0 GPa have been also studied. Volumes as a function of pressure, computed from the generalized gradient approximation, are closer to the experimental data than volumes calculated from the local density approximation. The crystal structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
0
17
1
Order By: Relevance
“…The pseudopotentials and basis sets used in this work were previously optimized for a set of dioctahedral 2:1 phyllosilicates (Ortega-Castro et al 2008). In a previous paper (Ortega-Castro et al 2010), the high-pressure behavior of Ms was calculated in both the local density approximation (LDA) with the Ceperley-Alder exchange-correlation functional (Ceperley and Alder 1980) and GGA-PBE approach, finding that the GGA yielded cell parameters closer to the experimental data than did LDA. In addition, White et al (2009) demonstrated that GGA functional showed lower energies and more accurate geometries.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pseudopotentials and basis sets used in this work were previously optimized for a set of dioctahedral 2:1 phyllosilicates (Ortega-Castro et al 2008). In a previous paper (Ortega-Castro et al 2010), the high-pressure behavior of Ms was calculated in both the local density approximation (LDA) with the Ceperley-Alder exchange-correlation functional (Ceperley and Alder 1980) and GGA-PBE approach, finding that the GGA yielded cell parameters closer to the experimental data than did LDA. In addition, White et al (2009) demonstrated that GGA functional showed lower energies and more accurate geometries.…”
Section: Methodsmentioning
confidence: 99%
“…This rotation is defined by the α angle. Crystal chemistry, pressure, and temperature affect the α angle (Comodi and Zanazzi 1997;Mercier et al 2006;Ortega-Castro et al 2010).…”
Section: Crystal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To accelerate the process it is necessary to fully understand the mechanisms that govern dehydration. Research has generally focused on the dehydration behaviour of the group of clay minerals classified as 2:1 dioctahedral aluminous phyllosilicates, such as the smectites, montmoronillonites, illites and vermicullites [1][2][3][4][5][6][7][8][9] . Typically the dehydroxylation of these materials is produced by a combination of two independent processes that occur in the calcination process 1,[10][11][12][13][14][15] : (1) the continuous loss of interlayer water (dehydration) and (2) the discontinuous loss of structural water (dehydroxylation).…”
Section: Introductionmentioning
confidence: 99%
“…No significant difference in the main lattice parameters was detected between these arrangements (Table 1). According to previous studies [49], the most stable arrangement is the meta configuration and the least stable is the ortho configuration. The difference in energy with respect to the meta configuration can be related to the distance between Mg 2+ in the octahedral lattice.…”
Section: Resultsmentioning
confidence: 80%